Evaluation of the role of metabolizing enzymes and transporter variants in ezetimibe pharmacokinetics - González-Iglesias, Eva; Ochoa, Dolores; Navares-Gómez, Marcos; Zubiaur, Pablo; Aldama, Marina; Torre, Tamara de la; Ríos-Rodríguez, Marta de los; Soria-Chacartegui, Paula; Rodríguez-Lopez, Andrea; Abad-Santos, Francisco; Novalbos, Jesús (Frontiers in Pharmacology, 2024)
Ezetimibe inhibits cholesterol uptake by modulation of intestinal sterol absorption. Currently, although some studies have shown alterations in ezetimibe levels caused by alterations in the ABCG5, ABCG8, NPC1L1 or UGT1A1 genes, there are no pharmacogenetic guidelines to confirm these biomarkers. The aim of this work was to evaluate the effect of 49 variants in 22 pharmacogenes related to metabolism and transport. A total of 96 healthy volunteers from four bioequivalence clinical trials of ezetimibe as monotherapy or in combination with simvastatin were studied. Blood samples were extracted for unconjugated ezetimibe plasma quantification and genotyping. No association of metabolizing enzyme variants with ezetimibe pharmacokinetic parameters was found. The results show some trends in the univariate analysis for ABCB1 rs2032582 or ABCC2 rs2273697 and Cmax (p univariate (puv) =0.056 and 0.087, respectively), which finally reach significance in the multivariate analysis (p multivariate (pmv) =0.049 and 0.048, respectively). Nevertheless, these results need to be validated in future studies.